SIMULASI PEMBEBANAN PADA RANGKA MESIN FUNGSI HYBRID PENGUPAS BIJIH JAGUNG BERBASIS ELEMEN HINGGA - SUKENDRO SASONGKO; HERI IRAWAN; Hanif Fakhriawan Zany (Otopro, 2022)
Preliminary investigation obtains that the elevation of the machine of about 150 cm ease man while operating the machine.  Free body diagram illustrates forces distribution on the supporting frame. Thus, virtual simulation of forces to the supporting frame applies finite element method to the stage investigating to load and stress-strain. Stress and displacement are investigated by using Von Misses method. Principal stress 1st order and 3th order also are applied for investigating stress -strain. The simulation results are revealed F1 = 17 lbf (68.6 N) and F2 = 11.023 lbf (49,03 N). The maximum stress appearing at the frame of machine is about of 0,09 Mpa. Displacement reaches maximum is at 0,01 mm. By applying safety factor to the machine frame, maximum stress to the machine frame is obtained 0,69 Mpa. So that, 1% displacement performs the machine frame is strong enough to support the machine. The timing process efficiency of multitasking machine is increase 15% higher than single tasking machine.